The impact of short-form video as electronic word-of-mouth on consumer visit intention: a comparison between Tiktok and Instagram - Eng, Shi Yee (2023)
Short Form Video (SFV) as an effective tool for electronic Word of Mouth (eWOM) can facilitate the exchange of opinions among consumers. Compared to static text comments, short videos are more interactive and can be more engaging. However, in a consumer's decision to visit a physical shop, audiences are not easily swayed by influencer endorsements. They carefully consider all aspects to ensure the usefulness of the food reviews they share. This study aims to investigate several factors including argument quality, source credibility, quantity of information, consumer attitudes, information usefulness, and information adoption. Based on the grounded theory of Information Adoption Modelling (IAM), the aim was to understand consumers' willingness to accept and adopt new information from short videos (electronic word-of-mouth). The study was conducted with Malaysian Generation Z, who follow short video recommendations from food bloggers or influencers on TikTok and Instagram.